SOCIO-PSYCHOLOGICAL FEATURES OF PROFESSIONAL SELF-AWARENESS AND CONSCIOUS PROFESSIONAL CHOICE IN STUDENTS (Web of Teachers: Inderscience Research, 2025)
This article discusses the socio-psychological features of professional self-awareness and conscious professional choice in students, and gives recommendations on the difficulties in professional self-awareness, stages of professional self-determination, factors influencing the process of professional self-determination, and recommendations for the formation of the process of professional self-awareness in students.